Composite material
Patent Information
- Application Number
- JP2023142881
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-04
- Publication Date
- 2025-03-14
AI Technical Summary
【0008】 本発明によれば、被着体の温度上昇を抑制する熱保護用途に好適な複合材料を提供することができる。
Smart Images

Figure 2025035676000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite material containing a resin and titanium dioxide particles, and more particularly to a composite material suitable for thermal protection applications that suppresses a temperature rise in an adherend. [Background technology]
[0002] In recent years, there has been much research into "metamaterials," artificial materials that exhibit interactions with electromagnetic fields of electromagnetic waves that cannot occur in natural materials. Metamaterials are expected to be used as optical materials that exhibit various functions with light, and a specific application example is the design of metamaterials that can efficiently produce radiative cooling phenomena and the like, and their use as thermal protection materials that suppress temperature increases in adherends. Such thermal protection materials can efficiently suppress temperature increases in articles that are exposed to high temperatures due to outdoor installations, for example, without consuming energy such as electricity, and therefore can be said to be materials that can contribute to environmental issues such as global warming.
[0003] Patent Document 1 describes an invention relating to a selective radiative cooling structure having a selective emission layer in which a specific amount of dielectric particles having a specific average diameter are dispersed in a polymer, and reports that the selective thermal emission can efficiently remove heat from an object. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Special Publication No. 2019-515967 Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a novel composite material, particularly a composite material suitable for thermal protection applications in which an increase in temperature of an adherend is suppressed. [Means for solving the problem]
[0006] As a result of extensive investigations aimed at solving the above problems, the inventors discovered that a composite material containing a resin and titanium dioxide particles can be prepared so as to satisfy specific conditions, thereby providing a composite material suitable for thermal protection applications in which an increase in temperature of an adherend is suppressed, and thus completed the present invention. That is, one aspect of the present invention is as follows.
[0007] <1> A composite material containing a resin and titanium dioxide particles, wherein a total content of the titanium dioxide particles is 5% by mass to 50% by mass with respect to a total amount of the composite material, and the titanium dioxide particles satisfy at least one condition selected from the group consisting of the following condition 1 and the following condition 2: Condition 1: The titanium dioxide particles contain titanium dioxide particles having a particle diameter of 0.17 μm to 0.22 μm, and the volume-based frequency F1 of the titanium dioxide particles having a particle diameter of 0.17 μm to 0.22 μm relative to the total amount of the titanium dioxide particles is 5% or more. Condition 2: The titanium dioxide particles contain titanium dioxide particles having a particle diameter of 2.5 μm to 3.1 μm, and the volume-based frequency F2 of the titanium dioxide particles having a particle diameter of 2.5 μm to 3.1 μm relative to the total amount of the titanium dioxide particles is 5% or more (however, when both Condition 1 and Condition 2 are satisfied, F1+F2≦100[%]). <2> The resin has a total light transmittance of 80% or more. <1> The composite material according to claim 1. <3> The resin includes polyimide. <1> or <2> The composite material according to claim 1. <4> The polyimide includes a structure derived from at least one diamine selected from the group consisting of a diamine represented by the following formula (A-1) and a diamine represented by the following formula (A-2): <3> The composite material according to claim 1. [ka] (In formula (A-1) and formula (A-2), L 1 each independently represents a divalent hydrocarbon group having 1 to 3 carbon atoms or a single bond (-), R1 and R 2 each independently represents a hydrocarbon group having 1 to 10 carbon atoms, h represents an integer of 0 to 10, and i represents an integer of 0 to 10. <5> The polyimide includes a structure derived from at least one selected from the group consisting of a tetracarboxylic dianhydride represented by the following formula (B-1) and a tetracarboxylic dianhydride represented by the following formula (B-2): <3> or <4> The composite material according to claim 1. [ka] (In formula (B-1) and formula (B-2), L 2 represents a single bond (-), an oxa group (-O-), a carbonyl group (>C=O), a sulfonyl group (>S(=O)2), or a divalent hydrocarbon group having 1 to 15 carbon atoms which may contain at least one substituent selected from the group consisting of a fluoro group (-F), an oxa group (-O-), a carbonyl group (>C=O), a sulfonyl group (>S(=O)2), and a tertiary amino group (>N-); 3 , R 4 and R 5 each independently represents a hydrocarbon group having 1 to 10 carbon atoms, j represents an integer of 0 to 2, k represents an integer of 0 to 3, and m represents an integer of 0 to 3. <6> The titanium dioxide particles satisfy both of the conditions 1 and 2. <1> ~ <5> 13. The composite material according to claim 12 . <7> The film has a thickness of 1 μm to 100 μm. <1> ~ <6> 13. The composite material according to claim 12 . <8> For thermal protection to suppress temperature rise of the adherend. <1> ~ <7> 13. The composite material according to claim 12 . Effect of the Invention
[0008] According to the present invention, a composite material suitable for thermal protection applications that suppresses a rise in temperature of an adherend can be provided. [Brief description of the drawings]
[0009] [Figure 1]FIG. 1 is a conceptual diagram (perspective view) showing a composite material containing a resin and titanium dioxide particles, which is one embodiment of the present invention ((a) is a composite material in which the titanium dioxide particles satisfy condition 1, (b) is a composite material in which the titanium dioxide particles satisfy condition 2, and (c) is a composite material in which the titanium dioxide particles satisfy both conditions 1 and 2). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] In explaining the present invention, specific examples will be given. However, the present invention is not limited to the following contents as long as it does not deviate from the spirit of the present invention, and can be modified appropriately.
[0011] <Composite materials> A composite material according to one embodiment of the present invention (hereinafter sometimes abbreviated as "composite material") is a composite material containing a "resin" and "titanium dioxide particles". The total content of the titanium dioxide particles is 5% by mass to 50% by mass based on the total amount of the composite material, and the titanium dioxide particles satisfy at least one condition selected from the group consisting of the following "Condition 1" and "Condition 2". Condition 1: The titanium dioxide particles contain "titanium dioxide particles having a particle diameter of 0.17 μm to 0.22 μm", and the volume-based frequency F1 of the "titanium dioxide particles having a particle diameter of 0.17 μm to 0.22 μm" relative to the total amount of titanium dioxide particles is 5% or more. Condition 2: The titanium dioxide particles contain "titanium dioxide particles having a particle diameter of 2.5 μm to 3.1 μm", and the volume-based frequency F2 of "titanium dioxide particles having a particle diameter of 2.5 μm to 3.1 μm" relative to the total amount of titanium dioxide particles is 5% or more (however, when both conditions 1 and 2 are satisfied, F1 + F2 ≦ 100[%]).
[0012] The inventors of the present invention have conducted extensive research in search of a composite material suitable for thermal protection applications that suppress temperature rise in an adherend, and as a result have discovered that 1) "titanium dioxide particles with a particle size of 0.17 μm to 0.22 μm" efficiently reflect visible light by interacting (resonating) with the electromagnetic field of visible light, and 2) "titanium dioxide particles with a particle size of 2.5 μm to 3.1 μm" efficiently reflect infrared light with wavelengths of 8 to 13 μm, which is known as the "atmospheric window," by interacting (resonating) with the electromagnetic field of infrared light. They discovered that by coating an adherend with a composite material of resin and "titanium dioxide particles with a particle size of 0.17 μm to 0.22 μm," it is possible to effectively suppress the amount of visible light reaching the adherend in places where visible light is irradiated; and further, that by coating an adherend with a composite material of resin and "titanium dioxide particles with a particle size of 2.5 μm to 3.1 μm," the "titanium dioxide particles with a particle size of 2.5 μm to 3.1 μm" diffusely reflect temperature-derived infrared light, and efficiently radiate (radiate) infrared light from the "atmospheric window."
[0013] The composite material is a composite material containing a resin and titanium dioxide particles, and composite material 11, composite material 12, and composite material 13 in FIG. 1 contain resin 101 and titanium dioxide particles 1021 and / or titanium dioxide particles 1022. The total content of titanium dioxide particles in composite material 11, composite material 12, and composite material 13 is in the range of 5 mass % to 50 mass % with respect to the total amount of the composite material. Furthermore, titanium dioxide particles 1021 are titanium dioxide particles having a particle diameter in the range of 0.17 μm to 0.22 μm, and in composite material 11 and composite material 13, the volume-based frequency F1 with respect to the total amount of titanium dioxide particles is 5% or more. Furthermore, titanium dioxide particles 1022 are titanium dioxide particles having a particle diameter in the range of 2.5 μm to 3.1 μm, and in composite material 12 and composite material 13, the volume-based frequency F2 with respect to the total amount of titanium dioxide particles is 5% or more. Therefore, composite material 11 is a composite material in which titanium dioxide particles satisfy condition 1, composite material 12 is a composite material in which titanium dioxide particles satisfy condition 2, and composite material 13 is a composite material in which titanium dioxide particles satisfy both conditions 1 and 2, and composite material 11, composite material 12, and composite material 13 each correspond to a composite material that is one embodiment of the present invention.
[0014] The shape, physical properties, etc. of the "resin," "titanium dioxide particles," "titanium dioxide particles having a particle diameter of 0.17 μm to 0.22 μm," "titanium dioxide particles having a particle diameter of 2.5 μm to 3.1 μm," and "composite material" will be described in detail below.
[0015] (resin) The specific type and physical properties of the resin in the present invention are not particularly limited and can be appropriately selected depending on the purpose, but the total light transmittance of the resin is preferably 80% or more, more preferably 85% or more, even more preferably 88% or more, and particularly preferably 90% or more. When the total light transmittance of the resin is within the above range, the composite material can efficiently reflect visible light. The total light transmittance can be measured based on the Japanese Industrial Standard JIS K7375:2008.
[0016] Examples of the polymer contained in the resin in the present invention include polyimide, polyamideimide, polyetherimide, polyamide, polycarbonate, polycycloolefin, epoxy resin, polyacrylate, polyester, etc., and it is preferable to contain polyimide. Hereinafter, "polyimide" will be described with specific examples.
[0017] The type of diamine (hereinafter sometimes abbreviated as "diamine") for producing polyimide is not particularly limited and can be appropriately selected depending on the purpose, but can be classified into diamines having (non-cyclic) aliphatic hydrocarbon skeletons, diamines having monocyclic aliphatic hydrocarbon skeletons, diamines having polycyclic aliphatic hydrocarbon skeletons, diamines having monocyclic aromatic hydrocarbon skeletons, and diamines having polycyclic aromatic hydrocarbon skeletons based on the hydrocarbon skeleton to which the amino group (-NH2) is bonded. The hydrocarbon skeleton of the diamine is a hydrocarbon skeleton that may contain at least one selected from the group consisting of a branched structure and a carbon-carbon unsaturated bond (carbon-carbon double bond and carbon-carbon triple bond). In addition, the hydrocarbon skeleton of the diamine may contain substituents other than the two amino groups (-NH2), and is considered to be a hydrocarbon skeleton that may contain as a substituent at least one selected from the group consisting of a fluoro group (-F), an oxa group (-O-), a thio group (-S-), a carbonyl group (>C=O), a hydroxyl group (-OH), a sulfonyl group (>S(=O)2), a dimethylsiloxy group (-Si(CH3)2O-), a primary amino group (-NH3) (meaning that it may become a triamine, etc.), a secondary amino group (-NH-), and a tertiary amino group (>N-).
[0018] As the diamine, "A diamine having a (non-cyclic) aliphatic hydrocarbon skeleton having 3 to 20 carbon atoms which may contain at least one group selected from the group consisting of a fluoro group (-F), an oxa group (-O-), a thio group (-S-), a carbonyl group (>C=O), a hydroxy group (-OH), a sulfonyl group (>S(=O)2), a dimethylsiloxy group (-Si(CH3)2O-), a primary amino group (-NH3), a secondary amino group (-NH-), and a tertiary amino group (>N-) as a substituent (hereinafter sometimes abbreviated as "aliphatic hydrocarbon diamine");" "A diamine having a monocyclic aliphatic hydrocarbon skeleton having 3 to 20 carbon atoms which may contain at least one group selected from the group consisting of a fluoro group (-F), an oxa group (-O-), a thio group (-S-), a carbonyl group (>C=O), a hydroxy group (-OH), a sulfonyl group (>S(=O)2), a dimethylsiloxy group (-Si(CH3)2O-), a primary amino group (-NH3), a secondary amino group (-NH-), and a tertiary amino group (>N-) as a substituent (hereinafter sometimes abbreviated as "monocyclic aliphatic hydrocarbon diamine");" "A diamine having a polycyclic aliphatic hydrocarbon skeleton having 6 to 30 carbon atoms which may contain at least one group selected from the group consisting of a fluoro group (-F), an oxa group (-O-), a thio group (-S-), a carbonyl group (>C=O), a hydroxy group (-OH), a sulfonyl group (>S(=O)2), a dimethylsiloxy group (-Si(CH3)2O-), a primary amino group (-NH3), a secondary amino group (-NH-), and a tertiary amino group (>N-) as a substituent (hereinafter, may be abbreviated as "polycyclic aliphatic hydrocarbon diamine");" "A diamine having a monocyclic aromatic hydrocarbon skeleton having 6 to 20 carbon atoms which may contain at least one group selected from the group consisting of a fluoro group (-F), an oxa group (-O-), a thio group (-S-), a carbonyl group (>C=O), a hydroxy group (-OH), a sulfonyl group (>S(=O)2), a dimethylsiloxy group (-Si(CH3)2O-), a primary amino group (-NH3), a secondary amino group (-NH-), and a tertiary amino group (>N-) as a substituent (hereinafter sometimes abbreviated as "monocyclic aromatic hydrocarbon diamine");" Examples of the diamine include "a diamine having a polycyclic aromatic hydrocarbon skeleton having 10 to 30 carbon atoms which may contain as a substituent at least one group selected from the group consisting of a fluoro group (-F), an oxa group (-O-), a thio group (-S-), a carbonyl group (>C=O), a hydroxy group (-OH), a sulfonyl group (>S(=O)2), a dimethylsiloxy group (-Si(CH3)2O-), a primary amino group (-NH3), a secondary amino group (-NH-), and a tertiary amino group (>N-) (hereinafter, sometimes abbreviated as "polycyclic aromatic hydrocarbon diamine").
[0019] Examples of the aliphatic hydrocarbon diamine include 1,2-diaminopropane, 1,4-diaminobutane, 1,5-diaminopentane, 1,6-diaminohexane, 1,7-diaminoheptane, 1,10-diaminodecane, 1,12-diaminododecane, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 3,3'-diamino-N-methyldipropylamine, 1,4-butanediol bis(3-aminopropyl)ether, and diethylene glycol bis(3-aminopropyl)ether. Examples of monocyclic aliphatic hydrocarbon diamines include 1,3-cyclohexanediamine, 1,4-cyclohexanediamine, 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, 1-amino-3-aminomethyl-3,5,5-trimethylcyclohexane (isophoronediamine), and bis(aminomethyl)norbornane. Examples of the polycyclic aliphatic hydrocarbon diamine include 4,4'-methylenebis(cyclohexylamine), 4,4'-methylenebis(2-methylcyclohexylamine), and the like. Examples of the monocyclic aromatic hydrocarbon diamine include m-xylylenediamine, p-xylylenediamine, 3-aminobenzylamine, and 4-aminobenzylamine. Examples of the polycyclic aromatic hydrocarbon diamine include diamines having a condensed polycyclic aromatic hydrocarbon skeleton such as 1,5-diaminonaphthalene, 1,8-diaminonaphthalene, and 1,6-diaminopyrene, and diamines having a plurality of monocyclic aromatic hydrocarbons and / or condensed polycyclic aromatic hydrocarbons as a skeleton such as 9,9-bis(4-aminophenyl)fluorene, 1,4-bis[2-(4-aminophenyl)-2-propyl]benzene, bis(3-aminophenyl)sulfone, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 3,3'-dimethylnaphthidine, 4,4'-diaminodiphenyl ether, and 2,2'-bis(trifluoromethyl)benzidine.
[0020] The diamine is preferably a diamine having a monocyclic aliphatic hydrocarbon skeleton having 3 to 20 carbon atoms, and more preferably a diamine represented by the following formula (A-1) or a diamine represented by the following formula (A-2). When at least one selected from the diamine represented by formula (A-1) and the diamine represented by formula (A-2) is used to produce a polyimide, the obtained polyimide contains a structure derived from at least one selected from the diamine represented by formula (A-1) and the diamine represented by formula (A-2). [ka] (In formula (A-1) and formula (A-2), L 1 each independently represents a divalent hydrocarbon group having 1 to 3 carbon atoms or a single bond (-), R 1 and R 2 each independently represents a hydrocarbon group having 1 to 10 carbon atoms, h represents an integer of 0 to 10, and i represents an integer of 0 to 10.
[0021] L 1 Each of them independently represents a "divalent hydrocarbon group having 1 to 3 carbon atoms" or a "single bond (-)". A "divalent hydrocarbon group" refers to a hydrocarbon group having two bonding positions, and a "single bond (-)" refers to L 1This means that the amino groups (-NH2) at both ends are directly bonded to the cyclohexyl skeleton (norbornane skeleton). L 1 Examples of the alkyl group include a methylene group (-CH2-), a single bond (-), and an ethylene group (-CH2CH2-), with a methylene group (-CH2-) and a single bond (-) being preferred.
[0022] R 1 and R 2 Each independently represents a hydrocarbon group having 1 to 10 carbon atoms, and R 1 and R 2 The hydrocarbon group preferably has 8 or less carbon atoms, more preferably 6 or less, and even more preferably 6 or less carbon atoms. R 1 and R 2 Examples of the alkyl group include a methyl group (-CH3), an ethyl group (-CH2CH3), a vinyl group (-CH=CH2), an n-propyl group (-CH2CH2CH3), an n-butyl group (-CH2CH2CH2CH3), and the like, with a methyl group (-CH3) and an ethyl group (-CH2CH3) being preferred.
[0023] Although i represents an integer of 0 to 10, it is preferably 6 or less, more preferably 3 or less, and particularly preferably 0.
[0024] Examples of the diamine represented by formula (A-1) include 1,4-cyclohexanediamine and 1,4-bis(aminomethyl)cyclohexane. [ka]
[0025] An example of the diamine represented by formula (A-2) is bis(aminomethyl)norbornane. [ka]
[0026] The cyclohexane skeleton in 1,4-cyclohexanediamine can have two types of geometric isomers, cis and trans, and the cis / trans ratio of the cyclohexane skeleton in 1,4-cyclohexanediamine is preferably 50 / 50 to 0 / 100, more preferably 30 / 70 to 0 / 100. The cyclohexane skeleton in 1,4-bis(aminomethyl)cyclohexane can also have two types of geometric isomers, cis and trans, and the cis / trans ratio of the cyclohexane skeleton in 1,4-bis(aminomethyl)cyclohexane is preferably 40 / 60 to 0 / 100, more preferably 20 / 80 to 0 / 100. The position of the aminomethyl group in bis(aminomethyl)norbornane is not particularly limited, but may include structural isomers with different positions of the aminomethyl group, or optical isomers including S and R isomers.
[0027] The type of tetracarboxylic dianhydride (hereinafter, sometimes abbreviated as "tetracarboxylic dianhydride") for producing polyimide is not particularly limited and can be appropriately selected depending on the purpose, but can be classified into tetracarboxylic dianhydrides having a (non-cyclic) aliphatic hydrocarbon skeleton, tetracarboxylic dianhydrides having a monocyclic aliphatic hydrocarbon skeleton, tetracarboxylic dianhydrides having a polycyclic aliphatic hydrocarbon skeleton, tetracarboxylic dianhydrides having a monocyclic aromatic hydrocarbon skeleton, and tetracarboxylic dianhydrides having a polycyclic aromatic hydrocarbon skeleton, based on the hydrocarbon skeleton to which the -C(=O)-OC(=O)- group is bonded. The hydrocarbon skeleton of the tetracarboxylic dianhydride is a hydrocarbon skeleton that may contain at least one type selected from the group consisting of a branched structure and a carbon-carbon unsaturated bond (carbon-carbon double bond and carbon-carbon triple bond). The hydrocarbon skeleton of the tetracarboxylic dianhydride may contain a substituent other than a -C(=O)-OC(=O)- group, and is a hydrocarbon skeleton which may contain, as a substituent, at least one selected from the group consisting of a fluoro group (-F), an oxa group (-O-), a carbonyl group (>C=O), a sulfonyl group (>S(=O)2), and a tertiary amino group (>N-).
[0028] The tetracarboxylic dianhydride is "A tetracarboxylic acid dianhydride having a (non-cyclic) aliphatic hydrocarbon skeleton having 3 to 20 carbon atoms, which may contain at least one substituent selected from the group consisting of a fluoro group (-F), an oxa group (-O-), a carbonyl group (>C=O), a sulfonyl group (>S(=O)2), and a tertiary amino group (>N-) (hereinafter, sometimes abbreviated as "aliphatic hydrocarbon acid dianhydride");" "A tetracarboxylic acid dianhydride having a monocyclic aliphatic hydrocarbon skeleton having 3 to 20 carbon atoms, which may contain at least one substituent selected from the group consisting of a fluoro group (-F), an oxa group (-O-), a carbonyl group (>C=O), a sulfonyl group (>S(=O)2), and a tertiary amino group (>N-) (hereinafter, sometimes abbreviated as "monocyclic aliphatic hydrocarbon dianhydride");" "A tetracarboxylic acid dianhydride having a polycyclic aliphatic hydrocarbon skeleton having 6 to 30 carbon atoms, which may contain at least one substituent selected from the group consisting of a fluoro group (-F), an oxa group (-O-), a carbonyl group (>C=O), a sulfonyl group (>S(=O)2), and a tertiary amino group (>N-) (hereinafter, sometimes abbreviated as "polycyclic aliphatic hydrocarbon acid dianhydride");" "A tetracarboxylic acid dianhydride having a monocyclic aromatic hydrocarbon skeleton having 6 to 20 carbon atoms, which may contain at least one substituent selected from the group consisting of a fluoro group (-F), an oxa group (-O-), a carbonyl group (>C=O), a sulfonyl group (>S(=O)2), and a tertiary amino group (>N-) (hereinafter, may be abbreviated as "monocyclic aromatic hydrocarbon dianhydride");" Examples of the tetracarboxylic acid dianhydride include "a polycyclic aromatic hydrocarbon skeleton having 10 to 30 carbon atoms, which may contain at least one substituent selected from the group consisting of a fluoro group (-F), an oxa group (-O-), a carbonyl group (>C=O), a sulfonyl group (>S(=O)2), and a tertiary amino group (>N-) (hereinafter, sometimes abbreviated as "polycyclic aromatic hydrocarbon dianhydride").
[0029] Examples of the aliphatic hydrocarbon dianhydride include 1,2,3,4-butanetetracarboxylic acid 1,2:3,4-dianhydride and ethylenediaminetetraacetic acid dianhydride. Examples of the monocyclic aliphatic hydrocarbon acid dianhydride include 1,2,3,4-cyclobutane tetracarboxylic dianhydride, 1,2,4,5-cyclohexane tetracarboxylic dianhydride, 1,2,3,4-cyclopentane tetracarboxylic dianhydride, bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride, bicyclo[2.2.2]octane-2,3,5,6-tetracarboxylic 2,3:5,6-dianhydride, and 5-(2,5-dioxotetrahydrofuryl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride. Examples of the polycyclic aliphatic hydrocarbon dianhydride include dicyclohexyl-3,4,3',4'-tetracarboxylic dianhydride. Examples of the monocyclic aromatic hydrocarbon dianhydride include pyromellitic anhydride. Polycyclic aromatic hydrocarbon dianhydrides include naphthalene-1,4,5,8-tetracarboxylic dianhydride and 2,3,6,7-naphthalenetetracarboxylic acid. Examples of the tetracarboxylic acid dianhydride include tetracarboxylic acid dianhydrides having a condensed polycyclic aromatic hydrocarbon skeleton such as 2,3:6,7-dianhydride, 3,4'-biphthalic acid anhydride, 4,4'-biphthalic acid anhydride, 4,4'-oxydiphthalic acid anhydride, 4,4'-(ethyne-1,2-diyl)diphthalic acid anhydride, 4,4'-(hexafluoroisopropylidene)diphthalic acid anhydride, 3,3',4,4'-diphenylsulfone tetracarboxylic acid dianhydride, 3,3',4,4'-benzophenone tetracarboxylic acid dianhydride, 3,4,9,10-perylene tetracarboxylic acid dianhydride, 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic acid anhydride, and 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride.
[0030] The tetracarboxylic dianhydride is preferably a tetracarboxylic dianhydride having a monocyclic aliphatic hydrocarbon skeleton having 3 to 20 carbon atoms, or a tetracarboxylic dianhydride having a polycyclic aromatic hydrocarbon skeleton having 10 to 30 carbon atoms, and more preferably a tetracarboxylic dianhydride represented by the following formula (B-1) or a tetracarboxylic dianhydride represented by the following formula (B-2). When at least one selected from the tetracarboxylic dianhydride represented by formula (B-1) and the tetracarboxylic dianhydride represented by formula (B-2) is used to produce a polyimide, the obtained polyimide contains a structure derived from at least one selected from the tetracarboxylic dianhydride represented by formula (B-1) and the tetracarboxylic dianhydride represented by formula (B-2). [ka] (In formula (B-1) and formula (B-2), L 2 represents a single bond (-), an oxa group (-O-), a carbonyl group (>C=O), a sulfonyl group (>S(=O)2), or a divalent hydrocarbon group having 1 to 15 carbon atoms which may contain at least one substituent selected from the group consisting of a fluoro group (-F), an oxa group (-O-), a carbonyl group (>C=O), a sulfonyl group (>S(=O)2), and a tertiary amino group (>N-); 3 , R 4 and R 5 each independently represents a hydrocarbon group having 1 to 10 carbon atoms, j represents an integer of 0 to 2, k represents an integer of 0 to 3, and m represents an integer of 0 to 3.
[0031] L 2 represents "a single bond (-)", "an oxa group (-O-)", "a carbonyl group (>C=O)", "a sulfonyl group (>S(=O)2)", or "a divalent hydrocarbon group having 1 to 15 carbon atoms which may contain at least one substituent selected from the group consisting of a fluoro group (-F), an oxa group (-O-), a carbonyl group (>C=O), a sulfonyl group (>S(=O)2), and a tertiary amino group (>N-) as a substituent", where "a divalent hydrocarbon group" refers to a hydrocarbon group having two bonding positions, and "a single bond (-)" refers to L.2 The phenyl groups at both ends of L are directly bonded to each other, and an "oxa group (-O-)" is defined as 2 The phenyl groups at both ends of L are bonded via an oxa group (-O-). A "carbonyl group (>C=O)" is a 2 The phenyl groups at both ends of L are bonded via a carbonyl group (>C=O), and a "sulfonyl group (>S(=O)2)" is defined as 2 This means that the phenyl groups at both ends of the bond are bonded via a sulfonyl group (>S(=O)2). 2 is a "divalent hydrocarbon group", the divalent hydrocarbon group is intended to be a hydrocarbon group which may contain at least one type selected from the group consisting of a cyclic structure, a branched structure, and a carbon-carbon unsaturated bond (a carbon-carbon double bond and a carbon-carbon triple bond). L 2 Examples of such an alkyl group include a single bond (-), an oxa group (-O-), a carbonyl group (>C=O), a sulfonyl group (>S(=O)2), a methylene group (-CH2-), an ethylene group (-CH2CH2-), an ethenylene group (-CH=CH-), an ethynylene group (-C≡C-), and a fluorene group (>C(C6H4)2), with a single bond (-), an oxa group (-O-), and a fluorene group being preferred.
[0032] R 3 , R 4 and R 5 Each independently represents a hydrocarbon group having 1 to 10 carbon atoms, and R 3 , R 4 and R 5 The hydrocarbon group preferably has 8 or less carbon atoms, more preferably 6 or less, and even more preferably 6 or less carbon atoms. R 3 , R 4 and R 5 Examples of the alkyl group include a methyl group (-CH3), an ethyl group (-CH2CH3), a vinyl group (-CH=CH2), an n-propyl group (-CH2CH2CH3), an n-butyl group (-CH2CH2CH2CH3), and the like, with a methyl group (-CH3) and an ethyl group (-CH2CH3) being preferred.
[0033] j represents an integer of 0 to 2, k represents an integer of 0 to 3, and m represents an integer of 0 to 3, and each is preferably 2 or less, more preferably 1 or less, and particularly preferably 0.
[0034] An example of the tetracarboxylic dianhydride represented by the formula (B-1) is pyromellitic anhydride. [ka]
[0035] Examples of the diamine represented by formula (A-2) include 4,4'-biphthalic anhydride, 4,4'-oxydiphthalic anhydride, and 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride. [ka]
[0036] The polyimide preferably contains a structure represented by the following formula (C-1) or a structure represented by the following formula (C-2) as a constituent unit. The structure represented by formula (C-1) is a structure derived from a diamine represented by formula (A-1) and a tetracarboxylic dianhydride represented by formula (B-2), that is, a structure that can be formed by the reaction of a diamine represented by formula (A-1) and a tetracarboxylic dianhydride represented by formula (B-2). The structure represented by formula (C-2) is a structure derived from a diamine represented by formula (A-2) and a tetracarboxylic dianhydride represented by formula (B-1), that is, a structure that can be formed by the reaction of a diamine represented by formula (A-2) and a tetracarboxylic dianhydride represented by formula (B-1). [ka] (In formula (C-1) and formula (C-2), L 1 each independently represents a divalent hydrocarbon group having 1 to 3 carbon atoms or a single bond (-), L 2represents a single bond (-), an oxa group (-O-), a carbonyl group (>C=O), a sulfonyl group (>S(=O)2), or a divalent hydrocarbon group having 1 to 15 carbon atoms which may contain at least one substituent selected from the group consisting of a fluoro group (-F), an oxa group (-O-), a carbonyl group (>C=O), a sulfonyl group (>S(=O)2), and a tertiary amino group (>N-); 1 and R 2 each independently represents a hydrocarbon group having 1 to 10 carbon atoms, R 3 , R 4 and R 5 each independently represents a hydrocarbon group having 1 to 10 carbon atoms, h represents an integer from 0 to 10, i represents an integer from 0 to 10, j represents an integer from 0 to 2, k represents an integer from 0 to 3, and m represents an integer from 0 to 3.
[0037] Examples of the structure represented by formula (C-1) include structures represented by the following formulas. [ka]
[0038] Examples of the structure represented by formula (C-2) include structures represented by the following formulas. [ka]
[0039] The polyimide preferably contains a structure represented by formula (C-1) and a structure represented by formula (C-2) as structural units, but may contain structures other than the structure represented by formula (C-1) and the structure represented by formula (C-2). When the polyimide contains a structure represented by formula (C-1), the total content of the structure represented by formula (C-1) as structural units (total charge amount of diamine and tetracarboxylic dianhydride when synthesizing polyimide (mass % assuming that the total charge mass of monomers is 100 mass %) is usually 20 mass % to 100 mass %, but is preferably 30 mass % or more, more preferably 50 mass % or more, even more preferably 60 mass % or more, and particularly preferably 75 mass % or more. When the total content of the structure represented by formula (C-1) as structural units is within the above range, the effect of suppressing the temperature rise of the adherend and the mechanical strength of the composite material can be maintained well.
[0040] When the polyimide contains a structure represented by formula (C-2), the total content of the structure represented by formula (C-2) as a constituent unit (the total amount of diamine and tetracarboxylic dianhydride charged when synthesizing the polyimide (mass %) assuming that the total charged mass of the monomers is 100 mass %) is usually 20 mass % to 100 mass %, but is preferably 30 mass % or more, more preferably 50 mass % or more, even more preferably 60 mass % or more, and particularly preferably 75 mass % or more. When the total content of the structure represented by formula (C-2) as a constituent unit is within the above range, the effect of suppressing the temperature rise of the adherend and the mechanical strength of the composite material can be maintained in a good condition.
[0041] The polyimide preferably contains a structure represented by formula (C-1) and a structure represented by formula (C-2) as constituent units, but may contain a structure other than the structure represented by formula (C-1) and the structure represented by formula (C-2). In addition, the arrangement of each structure is not particularly limited, and may be any of an alternating copolymer, a random copolymer, a block copolymer, etc.
[0042] The molecular weight of polyimide can be determined by its intrinsic viscosity η. If polyimide is insoluble in a solvent, it can be substituted by the intrinsic viscosity of polyamic acid. In general, polyamic acid is dissolved in N-methyl-2-pyrrolidone (NMP) to a concentration of 0.5 g / dL, and the average value measured three times at 25°C using an Ubbelohde viscometer is used. In the present invention, the intrinsic viscosity η is preferably 0.3 to 2.5 dL / g, more preferably 0.4 to 2.0 dL / g, more preferably 0.5 to 1.8 dL / g, and further preferably 0.6 to 1.5 dL / g. Furthermore, in consideration of film-forming properties, it is particularly preferable that the intrinsic viscosity η is 0.7 to 1.3 dL / g. When the intrinsic viscosity η of the polyimide is within the above range, the effect of suppressing the temperature rise of the adherend and the mechanical strength of the composite material can be maintained satisfactorily.
[0043] The glass transition temperature (Tg) of polyimide is usually 150°C to 350°C, but is preferably 180°C or higher, more preferably 200°C or higher, even more preferably 230°C or higher, particularly preferably 260°C or higher, and preferably 330°C or lower, more preferably 300°C or lower. When the glass transition temperature of polyimide is within the above range, the temperature rise suppression effect of the adherend and the mechanical strength of the composite material can be maintained well. The glass transition temperature of polyimide can be measured by a known method using thermomechanical analysis (TMA). For example, a polyimide film obtained by imidizing polyamic acid varnish is cut into a size of 5 mm wide x 22 mm long, and measured with a TMA device under conditions of an air atmosphere, a temperature rise rate of 5°C / min, and a tensile mode (100mN) to obtain a TMA curve, and the curves before and after the inflection point of the TMA curve due to the glass transition can be extrapolated to obtain the TMA curve.
[0044] The total resin content in the composite material is usually 50% by mass to 95% by mass relative to the composite material (when the composite material is taken as 100% by mass), but is preferably 60% by mass or more, more preferably 70% by mass or more, and even more preferably 75% by mass or more, and is preferably 95% by mass or less, and more preferably 90% by mass or less. If the total resin content is within the above range, the effect of suppressing the temperature rise of the adherend and the mechanical strength of the composite material can be maintained well.
[0045] (Titanium dioxide particles) The titanium dioxide particles in the present invention satisfy at least one condition selected from the group consisting of the above-mentioned condition 1 and condition 2, and condition 1 is that the volume-based frequency F1 of titanium dioxide particles having a particle diameter of 0.17 μm to 0.22 μm is 5% or more. The volume-based frequency F1 of titanium dioxide particles is preferably 5% or more, more preferably 10% or more, even more preferably 20% or more, particularly preferably 50% or more, and usually 70% or less. When the volume-based frequency F1 is within the above range, the effect of suppressing the temperature rise of the adherend can be well maintained. The volume-based frequency F1 of titanium dioxide particles (the same applies to the volume-based frequency F2 of titanium dioxide particles described later) can be measured by a particle size distribution measuring device using laser light diffraction and scattering.
[0046] Condition 2 is that the volume-based frequency F2 of titanium dioxide particles having a particle size of 2.5 μm to 3.1 μm is 5% or more, and the volume-based frequency F2 of titanium dioxide particles is preferably 5% or more, more preferably 10% or more, even more preferably 20% or more, particularly preferably 50% or more, and usually 70% or less. When the volume-based frequency F1 is within the above range, the effect of suppressing the temperature rise of the adherend can be well maintained.
[0047] The titanium dioxide particles in the present invention satisfy at least one condition selected from the group consisting of the above-mentioned condition 1 and condition 2, and it is particularly preferable that they satisfy both condition 1 and condition 2. A composite material that satisfies both condition 1 and condition 2 is a material that can more effectively suppress a temperature rise of an adherend.
[0048] Other physical properties of the titanium dioxide particles in the present invention are not particularly limited and can be appropriately selected depending on the purpose, but the average particle size of titanium dioxide particles satisfying condition 1 is usually 0.08 μm to 0.50 μm, but is preferably 0.10 μm or more, more preferably 0.12 μm or more, even more preferably 0.13 μm or more, particularly preferably 0.14 μm or more, and is preferably 0.45 μm or less, more preferably 0.40 μm or less, even more preferably 0.35 μm or less, and particularly preferably 0.30 μm or less. The average particle size of titanium dioxide particles satisfying condition 2 is usually 0.8 μm to 6.5 μm, but is preferably 1.0 μm or more, more preferably 1.2 μm or more, even more preferably 1.4 μm or more, particularly preferably 1.6 μm or more, and is preferably 6.0 μm or less, more preferably 5.0 μm or less, even more preferably 4.0 μm or less, particularly preferably 3.0 μm or less. The average particle size of titanium dioxide particles can be measured by a particle size distribution measuring device using laser light diffraction scattering.
[0049] The specific type and physical properties of the titanium dioxide particles in the present invention are not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include titanium dioxide particles obtained by subjecting titanium dioxide (hereinafter sometimes abbreviated as "titanium dioxide raw material"), which is a raw material, to a pulverization and / or crushing treatment. Note that "pulverization" means that a titanium dioxide raw material larger than the target particle size is used, and the titanium dioxide is destroyed so as to generate a new surface, thereby reducing the particle size. Also, "crushing" means that a titanium dioxide raw material in the form of aggregated particles, which are aggregated primary particles and secondary particles equivalent to or smaller than the target particle size, is used, and the aggregated particles are broken down into primary particles and secondary particles.
[0050] The apparatus used for the pulverization and / or disintegration treatment of titanium dioxide particles includes ultrafine grinding machines such as bead mills, and bead mills include wet bead mills and dry bead mills, with wet bead mills being particularly preferred. Use of a wet bead mill makes it easier to control the volume-based frequency F1 of titanium dioxide particles with a particle diameter of 0.17 μm to 0.22 μm and the volume-based frequency F2 of titanium dioxide particles with a particle diameter of 2.5 μm to 3.1 μm within the desired range.
[0051] The specific type and physical properties of the titanium dioxide raw material before the pulverization and / or crushing treatment are not particularly limited and can be appropriately selected depending on the purpose, but the average primary particle size of the titanium dioxide raw material (agglomerated particles) mainly intended to be crushed is usually 1.0 nm to 10.0 nm, but is preferably 1.2 nm or more, more preferably 1.4 nm or more, even more preferably 1.6 nm or more, particularly preferably 1.7 nm or more, and is preferably 7.0 nm or less, more preferably 6.0 nm or less, even more preferably 5.0 nm or less, particularly preferably 4.0 nm or less. The crystal system of titanium dioxide may be rutile type or anatase type, or a mixture of both.
[0052] Examples of titanium dioxide raw materials include "Super Titania F Series" (F-1, F-2, F-4A, F-6A, F-10) manufactured by Showa Denko K.K., "High Purity Titanium Oxide CR-EL / PT Series" (PT-301, PT-401M, PT-401L, PT-501R, CR-EL) manufactured by Ishihara Sangyo Kaisha, Ltd., (FTR-700, SX-3172) manufactured by Sakai Chemical Industry Co., Ltd., and (S2B001) manufactured by Fuji Titanium Industry Co., Ltd.
[0053] The total content of titanium dioxide particles in the composite material is 5% by mass to 50% by mass relative to the composite material (when the composite material is taken as 100% by mass), but is preferably 7% by mass or more, more preferably 10% by mass or more, and is preferably 45% by mass or less, more preferably 40% by mass or less, even more preferably 35% by mass or less, and particularly preferably 30% by mass or less. If the total content of titanium dioxide particles is within the above range, the effect of suppressing the temperature rise of the adherend and the mechanical strength of the composite material can be maintained well.
[0054] The composite material may contain compounds other than the resin and the titanium dioxide particles, for example, a solvent and an additive. The solvent is generally one capable of dissolving the resin, and specific examples thereof include N-methylpyrrolidone, 1,3-dimethyl-2-imidazolidinone, γ-butyrolactone, N,N-dimethylacetamide, toluene, xylene, cyclohexanone, and methyl ethyl ketone. Examples of the additives include antioxidants, heat stabilizers, lubricants, tackifiers, plasticizers, viscosity modifiers, antistatic agents, antibacterial agents, antifoaming agents, dispersants, and polymerization inhibitors.
[0055] The composite material is not particularly limited in its specific form as long as it contains a resin and titanium dioxide particles, and can be appropriately selected according to the purpose, but it may be in the form of a film, a membrane applied to an adherend, or a paint (varnish) before being applied to an adherend. In the case of a paint (varnish) containing a large amount of solvent, the total content of titanium dioxide particles in the composite material becomes very small, so in that case the solvent content is not taken into consideration.
[0056] When the composite material is in the form of a film or membrane, the thickness of the composite material is 1 μm to 100 μm, but is preferably 2 μm or more, more preferably 5 μm or more, and is preferably 80 μm or less, more preferably 50 μm or less, even more preferably 30 μm or less, and particularly preferably 20 μm or less. When the thickness of the composite material is within the above range, the effect of suppressing the temperature rise of the adherend and the mechanical strength of the composite material can be well maintained.
[0057] The use of the composite material is not particularly limited and can be appropriately selected depending on the purpose, but it is particularly preferable that the composite material be used for thermal protection to suppress a rise in temperature of an adherend.
[0058] (Method of manufacturing composite materials) The method for producing the composite material is not particularly limited, and the composite material can be produced by appropriately adopting known steps. Generally, the composite material can be produced by a production method including the following steps: A resin solution preparation step in which a resin solution in which a resin is dissolved in a solvent is obtained (hereinafter, may be abbreviated as "resin solution preparation step"). A grinding and crushing treatment step (hereinafter sometimes abbreviated as "grinding and crushing treatment step") of grinding and / or crushing a titanium dioxide raw material to obtain titanium dioxide particles so that the titanium dioxide particles satisfy at least one condition selected from the group consisting of the following condition 1 and the following condition 2: A grinding / crushing / mixing process (hereinafter sometimes abbreviated as the "grinding / crushing / mixing process") in which a titanium dioxide raw material is mixed with the resin solution obtained in the resin solution preparation process, and a composite material solution is obtained by grinding and / or crushing the titanium dioxide particles so that the titanium dioxide particles satisfy at least one condition selected from the group consisting of the following condition 1 and the following condition 2. Condition 1: The titanium dioxide particles contain titanium dioxide particles having a particle diameter of 0.17 μm to 0.22 μm, and the volume-based frequency F1 of the titanium dioxide particles having a particle diameter of 0.17 μm to 0.22 μm relative to the total amount of the titanium dioxide particles is 5% or more. Condition 2: The titanium dioxide particles contain titanium dioxide particles having a particle diameter of 2.5 μm to 3.1 μm, and the volume-based frequency F2 of the titanium dioxide particles having a particle diameter of 2.5 μm to 3.1 μm relative to the total amount of the titanium dioxide particles is 5% or more (however, when both conditions 1 and 2 are satisfied, F1 + F2 ≦ 100 A mixing process in which the titanium dioxide particles obtained in the crushing and disintegration process are mixed with the resin solution obtained in the resin solution preparation process to obtain a composite material solution (hereinafter, sometimes abbreviated as the "mixing process"). A coating process in which the composite material solution obtained in the mixing process or the pulverization / disintegration process is applied to obtain a coating film (hereinafter, sometimes abbreviated as the "coating process"). A film-forming process in which the coating film obtained in the coating process is dried to obtain a composite material film (hereinafter, sometimes abbreviated as "film-forming process").
[0059] Examples of methods for producing a composite material include a method that includes a resin solution preparation step, a pulverizing / disintegration treatment step, a mixing step, a coating step, and a film-forming step, and a method that includes a resin solution preparation step, a pulverizing / disintegration treatment / mixing step, a coating step, and a film-forming step. The "resin solution preparation process", "crushing and disintegration process", "crushing and disintegration process and mixing process", "mixing process", "coating process", "film formation process", etc. will be described in detail below.
[0060] The resin solution preparation process is a process for obtaining a resin solution in which a resin is dissolved in a solvent. Methods for preparing a resin solution include dissolving a solid resin in a solvent to obtain a resin solution, synthesizing a resin in a solvent and dissolving (dispersing) the resulting resin directly in the solvent to obtain a resin solution, and the like.
[0061] The solvent for the resin solution is usually one that can dissolve the resin, and specific examples thereof include N-methylpyrrolidone, 1,3-dimethyl-2-imidazolidinone, γ-butyrolactone, N,N-dimethylacetamide, toluene, xylene, cyclohexanone, and methyl ethyl ketone.
[0062] The pulverizing and disintegrating treatment step is a step of obtaining a treatment solution by pulverizing and / or disintegrating the titanium dioxide raw material so as to satisfy at least one condition selected from the group consisting of condition 1 and condition 2, but the specific type and physical properties of the titanium dioxide raw material before the pulverizing and / or disintegrating treatment are the same as those described above. The pulverizing and disintegrating treatment mixing step is a step of blending the titanium dioxide raw material with the resin solution obtained in the resin solution preparation step, and obtaining a composite material solution by pulverizing and / or disintegrating the titanium dioxide particles so as to satisfy at least one condition selected from the group consisting of condition 1 and condition 2, but the specific type and physical properties of the titanium dioxide raw material in the pulverizing and disintegrating treatment mixing step are also the same.
[0063] When the titanium dioxide raw material is pulverized and / or crushed by a bead mill in the pulverizing and crushing treatment step and the pulverizing and crushing mixing step, the setting conditions of the bead mill can be appropriately selected from known setting conditions.
[0064] The mixing step is a step of obtaining a composite material solution by blending the titanium dioxide particles obtained in the pulverizing / disintegrating treatment step with the resin solution obtained in the resin solution preparation step, but the mixing method and mixing conditions in the mixing step are not particularly limited, and known methods can be appropriately adopted. Note that, when the pulverizing / disintegrating treatment mixing step is included, the mixing step is not necessary.
[0065] The coating process is a process in which the composite material solution obtained in the mixing process or the pulverization / disintegration mixing process is applied to obtain a coating film. The coating method and coating conditions in the coating process are not particularly limited, and any known method can be appropriately adopted. For example, coating can be performed using a comma coater, spin coater, die coater, dispenser, etc.
[0066] The film-forming step is a step of drying the coating film obtained in the coating step to obtain a composite material film, and the drying method and drying conditions in the film-forming step are not particularly limited and any known method can be appropriately adopted, for example, drying using a floating oven, IR oven, etc. The drying temperature is 60°C to 300°C depending on the solvent used, and the drying time is, for example, 4 minutes to 5 hours. EXAMPLES
[0067] The present invention will be described in more detail below with reference to examples, but the examples can be modified as appropriate without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be construed as being limited to the specific examples shown below.
[0068] <Production Example (Production of Polyamic Acid Solution)> In a 500 mL separable flask equipped with a thermometer, a stirrer, and a nitrogen inlet tube, 11.42 g (0.1 mol) of 1,4-cyclohexanediamine (Tokyo Chemical Industry Co., Ltd., trans isomer ratio: 99% or more. Hereinafter, sometimes abbreviated as "CHDA") and 228 g of an organic solvent N-methylpyrrolidone (Fujifilm Wako Pure Chemical Industries, Ltd., ultra-dehydrated grade. Hereinafter, sometimes abbreviated as "NMP") were added and stirred under a nitrogen stream to obtain a uniform solution. Furthermore, 28.98 g (0.985 mol) of 4,4'-biphthalic anhydride (Mitsubishi Chemical Co., Ltd., hereinafter sometimes abbreviated as "BPDA") was added all at once in powder form to the solution, and the mixture was heated in an oil bath maintained at 90°C to 100°C while being thoroughly stirred in a slurry state, and a reaction was carried out. The reaction was stopped 10 minutes after the sudden heat generation and the precipitation of a white solid was visually confirmed, and the temperature was naturally lowered to room temperature. As the reaction proceeded, the white precipitate dissolved, and a transparent, viscous polyamic acid solution was obtained. The viscosity of this polyamic acid solution measured with an E-type viscometer was 55,000 mPa s at 25°C. The solution was further diluted with 98 g of NMP to obtain a polyamic acid solution with a viscosity of 5,200 mPa s at 25°C. The η inh The viscosity was 1.2 and the solid content was 11% by mass.
[0069] <Preparation of titanium dioxide particles a> As one of the titanium dioxide particles to be used, "high-purity titanium dioxide PT-401L" manufactured by Ishihara Sangyo Kaisha, Ltd. was prepared as titanium dioxide particles a.
[0070] <Preparation of titanium dioxide particles b> As the titanium dioxide raw material, Ishihara Sangyo Kaisha, Ltd.'s "High Purity Titanium Oxide PT-401L" was prepared, and 1.22 g of this was added to 100 g of the polyamic acid solution produced in the Production Example. This was then subjected to a crushing and disintegration treatment using a Bead Mill Labostar Mini MGF015 (bead diameter: 0.8 mm, peripheral speed: 10 m / s, processing time: 60 min) manufactured by Ashizawa Finetech Co., Ltd., to prepare a mixture of titanium dioxide particles b, in which the aggregated particles had been crushed, and polyamic acid. During the disintegration treatment using the bead mill, the secondary current value increased, causing an overload state, so the peripheral speed was gradually reduced to 7 m / s.
[0071] <Preparation of titanium dioxide particles c)> As one of the titanium dioxide particles to be used, "SX-3172" manufactured by Sakai Chemical Industry Co., Ltd. was prepared as titanium dioxide particles c.
[0072] <Measurement of particle size distribution of titanium dioxide particles and volume-based frequency F1 and frequency F2> The average particle size and particle size distribution of each of the titanium dioxide particles a, titanium dioxide particles b, and titanium dioxide particles c were measured under the following conditions using a Microtrac MT300EXII manufactured by Microtrac Corporation, and the volume-based frequency F1 of titanium dioxide particles with a particle size of 0.17 μm to 0.22 μm and the volume-based frequency F2 of titanium dioxide particles with a particle size of 2.5 μm to 3.1 μm were observed. The results are shown in Table 1. Particle size distribution measurement conditions ·Circulation speed: 50% (at 100%, 65mL / sec) Dispersion solvent: NMP (Fujifilm Wako Pure Chemical Industries, Ltd., special grade reagent) Dispersing agent: None Dispersion method: Circulation within the device only (no ultrasonic dispersion treatment)
[0073] [Table 1]
[0074] <Example 1> (Preparation of polyamic acid solution B-1 containing titanium dioxide particles) The mixture of titanium dioxide particles b and polyamic acid prepared in <Preparation of titanium dioxide particles b> was used as polyamic acid solution B-1 containing titanium dioxide particles. The content of polyamic acid in 100 g of polyamic acid solution B-1 was 11 g, and the content of titanium dioxide relative to the total (100 mass%) of titanium dioxide and polyamic acid was 10.0 mass%.
[0075] (Production of composite membrane B-2) The polyamic acid solution B-1 was uniformly applied to a KBr substrate of 25 mmΦ×2 mmt size using a spin coater under the conditions of 1500 rpm×15 sec+1700 rpm×5 sec. Then, it was immediately placed in an inert oven under a nitrogen atmosphere kept at 50°C, and the temperature was raised to 280°C over 2 hours, and then it was kept at 2800°C for another 2 hours for complete drying and imidization. It was allowed to cool naturally to room temperature under the nitrogen atmosphere, and then it was taken out to form a composite material film B-2 on the KBr substrate. The thickness of the composite material film B-2 was 6 μm.
[0076] <Example 2> (Preparation of polyamic acid solution C-1 containing titanium dioxide particles and fabrication of composite membrane C-2) To 100 g of the polyamic acid solution produced in the production example, 1.22 g of titanium dioxide particles c was added, and the mixture was thoroughly kneaded in a rotation-revolution type stirrer (UNIX uni-cycloneUM-118) under the conditions of revolution 1600 rpm, rotation 700 rpm x 3 min and revolution 1600 rpm, rotation 200 rpm x 1 min to obtain polyamic acid solution C-1. The obtained polyamic acid solution C-1 was used to form a composite material film C-2 on a KBr substrate by the same method as in Example 1. The thickness of the composite material film C-2 was 6 μm.
[0077] <Comparative Example 1> (Preparation of polyimide solution A-1 containing titanium dioxide particles and preparation of composite membrane A-2) A polyimide solution A-1 was obtained in the same manner as in Example 2, except that titanium dioxide particles a were used instead of titanium dioxide particles c in Example 2. Furthermore, a composite material film A-2 was formed on a KBr substrate in the same manner as in Example 1. The thickness of the composite material film A-2 was 6 μm.
[0078] <Simulated solar irradiation test and surface temperature measurement for composite membrane> The composite material film B-2 obtained in Example 1, the composite material film C-2 obtained in Example 2, the composite material film A-2 obtained in Comparative Example 1, and the KBr substrate on which no composite material film was formed (referred to as Comparative Example 2) were each irradiated with simulated sunlight for 180 seconds using a solar simulator HAL-320 manufactured by Asahi Spectroscopic Co., Ltd. The light source of the HAL-320 was an AM1.5G simulated sun. In addition, the surface temperature rise after 180 seconds of irradiation was measured using an infrared thermography FLIR ETS320 manufactured by FLIR Systems, Inc., based on the surface temperature at 0 seconds of irradiation. The results are shown in Table 2.
[0079] [Table 2]
[0080] From Table 2, it is clear that composite material film B-2 of Example 1, in which the total content of titanium dioxide particles is 5% by mass to 50% by mass with respect to the total amount of the composite material and the volume-based frequency F1 of titanium dioxide particles having particle diameters of 0.17 μm to 0.22 μm with respect to the total amount of titanium dioxide particles is 5% or more, and composite material film C-2 of Example 2, in which the total content of titanium dioxide particles is 5% by mass to 50% by mass with respect to the total amount of the composite material and the volume-based frequency F2 of titanium dioxide particles having particle diameters of 2.5 μm to 3.1 μm with respect to the total amount of titanium dioxide particles is 5% or more, can effectively suppress the rise in surface temperature compared to composite material film A-2 of Comparative Example 1 which does not satisfy the frequencies F1 and F2, and Comparative Example 2 which does not have a composite material film. [Industrial Applicability]
[0081] The composite material according to one embodiment of the present invention can be used as a thermal protection material that suppresses an increase in temperature of an adherend. [Explanation of symbols]
[0082] 11 Composite material in which titanium dioxide particles satisfy condition 1 12 Composite material in which titanium dioxide particles satisfy condition 2 13 Composite material in which titanium dioxide particles satisfy conditions 1 and 2 101 Resin 1021 Titanium dioxide particles with particle size of 0.17μm to 0.22μm 1022 Titanium dioxide particles with particle size of 2.5μm to 3.1μm
Claims
1. A composite material containing a resin and titanium dioxide particles, the total content of the titanium dioxide particles is 5% by mass to 50% by mass based on the total amount of the composite material; The composite material, wherein the titanium dioxide particles satisfy at least one condition selected from the group consisting of the following condition 1 and the following condition 2: Condition 1: The titanium dioxide particles contain titanium dioxide particles having a particle diameter of 0.17 μm to 0.22 μm, and the volume-based frequency F of the titanium dioxide particles having a particle diameter of 0.17 μm to 0.22 μm relative to the total amount of the titanium dioxide particles is 1 However, it is more than 5%. Condition 2: The titanium dioxide particles contain titanium dioxide particles having a particle diameter of 2.5 μm to 3.1 μm, and the volume-based frequency F of the titanium dioxide particles having a particle diameter of 2.5 μm to 3.1 μm relative to the total amount of the titanium dioxide particles is 2 is 5% or more (however, when both the condition 1 and the condition 2 are satisfied, F 1 +F 2 ≦100[%]).
2. The composite material according to claim 1 , wherein the resin has a total light transmittance of 80% or more.
3. The composite material of claim 1 , wherein the resin comprises a polyimide.
4. The composite material according to claim 3, wherein the polyimide comprises a structure derived from at least one diamine selected from the group consisting of a diamine represented by the following formula (A-1) and a diamine represented by the following formula (A-2): 【Chemistry 1】 (In formula (A-1) and formula (A-2), L 1 each independently represents a divalent hydrocarbon group having 1 to 3 carbon atoms or a single bond (-), R 1 and R 2 each independently represents a hydrocarbon group having 1 to 10 carbon atoms, h represents an integer of 0 to 10, and i represents an integer of 0 to 10.
5. The composite material according to claim 3, wherein the polyimide comprises a structure derived from at least one selected from the group consisting of a tetracarboxylic dianhydride represented by the following formula (B-1) and a tetracarboxylic dianhydride represented by the following formula (B-2): 【Chemistry 2】 (In formula (B-1) and formula (B-2), L 2 is a single bond (-), an oxa group (-O-), a carbonyl group (>C=O), a sulfonyl group (>S(=O) 2 ), or as a substituent, a fluoro group (-F), an oxa group (-O-), a carbonyl group (>C=O), a sulfonyl group (>S(=O) 2 a divalent hydrocarbon group having 1 to 15 carbon atoms which may contain at least one selected from the group consisting of a tertiary amino group (>N-), and a tertiary amino group (>N-), 3 , R 4 and R 5 each independently represents a hydrocarbon group having 1 to 10 carbon atoms, j represents an integer of 0 to 2, k represents an integer of 0 to 3, and m represents an integer of 0 to 3.
6. The composite material according to claim 1 , wherein the titanium dioxide particles satisfy both of the conditions 1 and 2.
7. The composite material according to claim 1 , which is in the form of a film having a thickness of 1 μm to 100 μm.
8. The composite material according to claim 1, which is used for thermal protection to suppress a rise in temperature of an adherend.
Citation Information
Patent Citations
Radiative cooling structures and systems
JP2019515967A